Climate Change Policies in Germany Make Ambition Pay - Klein, Caroline (OECD Economics Department Working Papers, 2012)
Germany reduced greenhouse gas emissions substantially but remains an important emitter. Ambitious targets for climate change mitigation have been fixed and a broad range of environmental measures are being implemented. The efficiency of these measures, as well as their coordination, should be improved though, as reaching the targets risks being costly. In particular, the early phase-out of nuclear power and the development of renewable energy sources will require high levels of investment and public financial support. Establishing a clear carbon price in all sectors of the economy and phasing out environmentally harmful subsidies would contribute to reducing the CO2 abatement cost. The generosity of feed-in tariffs also needs to be carefully monitored and adjusted tightly in line with market developments to avoid deadweight losses and excessive increases in electricity prices. In addition, in order to maintain the German leadership in green sectors and preserve future sources of growth, competition in the energy sectors should be increased and eco-innovation further developed. This Working Paper relates to the 2012 Economic Survey of Germany, www.oecd.org/eco/surveys/germany